The modified Medical Research Council scale misclassifies exertional breathlessness among people referred for exercise testing - David Gustafsson; Viktor Elmberg; Linus Schiöler; Dennis Jensen; Magnus Ekström (ERJ Open Research, 2023)
Background Exertional breathlessness is a major symptom in cardiorespiratory disease and is often assessed using the modified Medical Research Council (mMRC) questionnaire. The mMRC might underestimate exertional breathlessness in people with impaired exercise capacity who have reduced their physical activity to avoid the symptom. We aimed to evaluate the ability of mMRC to detect abnormally high exertional breathlessness or abnormally low exercise capacity during incremental cycle exercise testing (IET). Methods A secondary analysis of data from a randomised controlled trial of outpatients aged 18 years or older referred for IET was carried out. Participants completed the mMRC before IET. Abnormally high exertional breathlessness was defined as a breathlessness (Borg 0–10) intensity response more than the upper limit of normal. Abnormally low exercise capacity was defined using published reference equations. The sensitivity, specificity, accuracy and discriminative ability of each mMRC rating to detect each outcomewas calculated. Results 92 participants were included; the mean age was 59 years, 61% were male, and 64% and 15% had mMRC 1 and ≥2, respectively. An mMRC ≥2 had the highest accuracy (71%) to detect abnormally high exertional breathlessness, with a specificity of 93% but a sensitivity of only 28%, failing to identify 72% of people with abnormally high exertional breathlessness. The accuracy, specificity and sensitivity for abnormally low exercise capacity was 64%, 88% and 19%, respectively. Conclusion Among people referred for clinical exercise testing, the mMRC dyspnoea scale misclassified exertional breathlessness and exercise capacity assessed using cycle IET, with substantial underdetection. A mMRC dyspnoea rating of 0–1 does not preclude the presence of abnormally high exertional breathlessness or abnormally low exercise capacity.